The effectiveness of Group Play Therapy to Reducing Teacher-Children Relationship Teaching Stress in Primary Schools - Gholam reza Rajabi; Maryam Pouremami (مطالعات روانشناسی تربیتی)
This research aims to the effectiveness of group play therapy on reducing the teacher-student relationship teaching stress in Sardasht-Dezful primary schools and its surrounding villages in a semi-experimental design with pre-test, post-test, and follow-up was conducted with the control group. The population of this research included all girls', boys' and mixed elementary schools of Sardasht-Dezful city and its surrounding villages (526 students) in the academic year of 2021-2022. For sample selection, five girls', boys', and mixed schools were randomly selected among 117 elementary schools in this city and its surrounding villages. ]n the next stage, 30 students were selected using the teachers and counselors reports and confirmation of the behavioral disorders center of this city in according to emotional and behavioral disorders criteria, that 15 students were randomly assigned to the experimental group and 15 students randomly to the control group. Teachers responded to the Index of Teaching Stress in three stages: pre-test, post-test, and follow-up for each student. The students of the experimental group participated in ten forty-five minute group play therapy intervention sessions, and the students of the control group did not receive any intervention. The data were analyzed using the statistical method of repeated measure analysis of variance (mixed) and SPSS-22 statistical software. The results showed that group play therapy has reduced of the teacher-student relationship teaching stress the experimental group students in compare with control group participants (p < 0.01). Also, the scores of the group under group play therapy intervention of the pre-test to follow-up stage in hyperactivity, anxiety/withdrawal, behavioral/aggression disorder, and hopelessness in working with parent’s variables have decreased, but was not observed change in disrupts teaching process variable. Therefor, it is possible to use this type of group therapy play to reduce teacher-student relationship teaching stress. group play therapy is effective in reducing teacher-student relationship teaching stress.